Interactions of amyloidogenic proteins with mitochondrial protein import machinery in aging-related neurodegenerative diseases - Reed, Ashley L.; Mitchell, Wayne; Alexandrescu, Andrei T.; Alder, Nathan N. (Frontiers in Physiology, 2023)
Most mitochondrial proteins are targeted to the organelle by N-terminal mitochondrial targeting sequences (MTSs, or ‘presequences’) that are recognized by the import machinery and subsequently cleaved to yield the mature protein. MTSs do not have conserved amino acid compositions, but share common physicochemical properties, including the ability to form amphipathic α-helical structures enriched with basic and hydrophobic residues on alternating faces. The lack of strict sequence conservation implies that some polypeptides can be mistargeted to mitochondria, especially under cellular stress. The pathogenic accumulation of proteins within mitochondria is implicated in many aging-related neurodegenerative diseases, including Alzheimer’s, Parkinson’s, and Huntington’s diseases. Mechanistically, these diseases may originate in part from mitochondrial interactions with amyloid- precursor protein (APP) or its cleavage product β-amyloid (Aβ), α-synuclein (α-syn), and mutant forms of huntingtin (mHtt), respectively, that are mediated in part through their associations with the mitochondrial protein import machinery. Emerging evidence suggests that these three amyloidogenic proteins may present cryptic targeting signals that act as MTS mimetics and can be recognized by mitochondrial import receptors and transported into different mitochondrial compartments. Accumulation of these mistargeted proteins could overwhelm the import machinery and its associated quality control mechanisms, thereby contributing to neurological disease progression. Alternatively, the uptake of amyloidogenic proteins into mitochondria may be part of a protein quality control mechanism for clearance of cytotoxic proteins. Here we review the pathomechanisms of these diseases as they relate to mitochondrial protein import and effects on mitochondrial function, what features of APP/Aβ, α-syn and mHtt make them suitable substrates for the import machinery, and how this information can be leveraged for the development of therapeutic interventions.